Design of remotely operated vehicle as installer tools of tidal turbine and seismograph under water - Muhammad Sulthan Mazaya (Institute of Advanced Engineering and Science, 2019)
Tidal turbines and seismographs constitute instruments that can be used as an earthquake detector that lead to tsunamis. As an early detection instrument for tsunami disaster, tidal turbine and seismograph are generally placed under the surface of the water. The design objective in this study is designing a Remotely Operated Vehicle (ROV) which can be used as a tool for tidal turbine and seismograph installation. The design method applied in this study is designing a prototype by following the product research and development procedures. Making control systems has three stages, namely: software design, hardware manufacture, and software and hardware integration. The made software includes the ROV motion control program through the control of Arduino Nano R2 ATMega microcontroller with programming that uses C-Basic language. The design findings show that the designed ROV can be used effectively to simulate the installation of tidal turbine and seismograph under the surface of the water in 2 meters at depth with 15 minutes of installation time in undulating water.